Acidulates performance for the better efficacy of rock phosphate in wheat (Triticum aestivum) - KUMAR, RAJEEW; KRISHNA, MAYA; BHATNAGAR, A; PANDEY, D S; SINGH, V P; PANDEY, PRIYANKA (The Indian Journal of Agricultural Sciences, 2019)
Fixed plot field experiments were conducted at G B Pant University of Agriculture and Technology, Pantnagar, Uttarakhand during 2009–10 to 2012–13, to screen acidulates for better utilization of rock-phosphate in wheat (Triticum aestivum L.). Acidulates used were gypsum, SSP, FYM, pressmud (PM) and phosphorus solubilizing bacteria (PSB), in different ratio with rock phosphate. The experiment was conducted in RBD with eight treatments replicated thrice. Results revealed that RP acidulated with gypsum gave maximum grain yield (44.2 q/h) and straw yield (68.2 q/h) which were found significantly higher than the other treatments except pressmud acidulation. Plant height, spike length, number of fertile and sterile spikelet/spike and 1000 grain weight were found non-significant due to the treatments but maximum value was obtained with gypsum acidulation. Tillers and dry matter accumulations were also significantly higher in gypsum acidulated plots than the other treatments. Maximum soil available N was noticed in pressmud and PSB acidulated plot, which was found at par with FYM and pressmud treatments. Soil available P was found maximum in gypsum acidulated RP plots which was found at par with FYM+PSB acidulates RP and significantly higher than other treatments. In case of soil available K, SSP acidulated RP gave maximum value which was significantly higher than the other treatments. Nutrient uptake in gypsum acidulated RP was higher as compared to other treatments. Highest gross return (` 65678.3 h), net return (` 44504.5 h) and benefit:cost ratio (2.10) was also recorded in gypsum acidulates.